Abnormal Propeptide Processing Resulting in the Presence of Two Abnormal Species of Protein C in Plasma - Simioni, Paolo; Kalafatis, Michael; Tormene, Daniela; Luni, Sonia; Zerbinati, Patrizia; Barzon, Luisa; Palù, Giorgio; Girolami, Antonio (Thrombosis and Haemostasis, 2001)
A heterozygous GT transversion at position 1388 of the protein C (PC) gene which predicted the substitution of Arg-1 to a Leu (PCR-1L) was identified in a thrombophilic patient. The PCR-1L was purified from the patient’s plasma by immunoaffinity chromatography using Ca++-independent and Ca++-dependent monoclonal antibodies. NH2-terminal sequencing of the light chain of PCR-1L revealed two amino acid sequences: one was identical to the complete propeptide sequence of PC, while the other matched the normal PC light chain sequence elongated by one amino acid (Leucine at position 1). Activated PCR-1L/propeptide exhibited normal amidolytic and impaired anticoagulant activity. Thus, the substitution of a Leu for an Arg at position -1 of PC shifts the propeptidase cleavage site by one amino acid. In addition, in PCR-1L/propeptide the propeptide cleavage at Lys-2 is less efficient since approximately 60% of PC variant molecules present in patient’s plasma retained the entire propeptide. Our findings suggest that depending on the specific amino acid substitution at position-1, PC can be secreted in plasma containing the entire propeptide attached to the light chain. Impaired interaction of elongated APC molecules with a membrane-surface and/or factor Va which is the physiological substrate for APC, is manifested in vivo by thrombophilia.
Keywords: Dysfunctional protein C; type II defect; propeptide clearage; thrombophilia; factor V